HiperLAN/2: OFDM simulation using Simulink / Nor Azrina Mohammad Yusuf - Mohammad Yusuf, Nor Azrina (2004)
Orthogonal Frequency Division Multiplexing (OFDM) is the digital modulation technique, which consists of transmitting a data stream on several carriers instead of using single carrier. It is adopted in several recent digital wireless broadcast and network standards, including HiperLAN/2, IEEE802.1 la and Digital audio Broadcasting (DAB). This project paper will explore the use of Simulink to model features of OFDM receiver design. This thesis will also discuss the implementation of OFDM in HiperLAN/2 by simulation using Simulink. It will also explore the use of Simulink to model features of OFDM receiver designs, in packet based and in continuous transmission system, including synchronization and channel compensation problems.